PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING SISWA SEKOLAH DASAR - Luthfiana, Maria; Mulyono, Dodik; Yanto, Yufitri; Muharpriliana, Adelia; Syakirah, Jihan (LP4MK STKIP PGRI Lubuklinggau, 2024)
This research aims to improve elementary school students' mathematical problem-solving abilities by using a Problem Based Learning Model. This research was carried out at SD Negeri 54 Lubuklinggau. The type of research used was Classroom Action Research (PTK) with the research subjects being 25 students in class Vb of SD Negeri 54 Lubuklinggau. Data collection techniques use test, observation and documentation methods. The data analysis techniques used are qualitative descriptive and quantitative descriptive. The research consists of two cycles and each cycle consists of four stages, namely planning, implementing actions, observing and reflecting. The results of this research show that the application of the Problem Based Learning (PBL) learning model can improve students' mathematical problem-solving abilities, namely from cycle I to cycle II by 24.25% from the poor to good category. With this it can be concluded that the Problem Based learning model can be used as an alternative learning model.